Pelatihan Penyusunan Proposal Penelitian dan Pengabdian Kepada Masyarakat Berbasis Hibah - Azhari, Azhari; Mukhlis, Mukhlis; Musrizal, Musrizal; Syahrin, Alfi (Aceh Journal of Community Engagement (AJCE), 2022)
This service activity aims to improve the understanding and ability of lecturers at STIT Al-Washliyah Aceh Tengah regarding the preparation of research proposals and community service based on Grants. the participants involved in this service activity are lecturers and education staff at STIT Al-Washliyah Aceh Tengah. The stages carried out in this service consist of two stages, namely the delivery of material and the practice of preparing proposals. The material presented is a strategy for preparing research proposals and community service in higher education, using the lecture method and proposal review. The result of this service is an increase in the understanding and ability of lecturers and education staff regarding the preparation of proposals. The results of this service can be used as input for lecturers and education staff to improve the professionalism and competence of lecturers in teaching and careers.